Metabolomics Deciphers Potential Targets of Xuefu Zhuyu Decoction Against Traumatic Brain Injury in Rat - Li, Teng; Hu, En; Li, Pengfei; Yang, Zhaoyu; Wu, Yao; Ding, Ruoqi; Zhu, Xiaofei; Tang, Tao; Wang, Yang (Frontiers in Pharmacology, 2020)
Xuefu Zhuyu decoction (XFZYD) performs multiple functions for traumatic brain injury (TBI) treatment. However, its clinical application is limited by the incomplete exploration of targets and inadequate discussion of mechanisms. We aimed to investigate the metabolic alterations of XFZYD in acute and chronic stages of TBI. Sprague-Dawley rats were randomly divided into the sham, controlled cortical impact (CCI) and XFZYD group. Behavioral and histopathological tests were used to evaluate the neuroprotective effects. Coagulation assays were performed to assess safety. Moreover, we analyzed the metabolomic profiling of hippocampal samples with different time intervals after CCI by high-performance liquid chromatography-tandem mass spectrometry (HPLC-MS/MS). Differential metabolites were screened by multivariate data analysis. To further uncover the association between candidate metabolites and biological interaction networks, we applied bioinformatics analysis using MetaboAnalyst 4.0, STITCH 5.0 and TCMSP. The potential mechanism was verified by ELISA and western blot. XFZYD meliorated neurological deficiencies post-CCI without impairing blood coagulation in the rat's model. Seventeen and fourteen metabolites were filtered on d 3 and 21, respectively. Eleven of potential metabolites were common at these time points, involving two significant pathways (arginine and proline metabolism, phenylalanine, tyrosine and tryptophan biosynthesis). Gamma-aminobutyric acid (GABA) and the related pathways were specifically affected by XFZYD at the acute phase of TBI, while biosynthesis of amino acids was the major pathway influenced at the chronic phase. This study provides broad insights into the therapeutic effects of XFZYD in treating TBI through the whole phases.